Utilization of biochar impregnated with anaerobically digested slurry as slow‐release fertilizer. Issue 1 (19th August 2013) - Oh, Taek‐Keun; Shinogi, Yoshiyuki; Lee, Seung‐Joo; Choi, Bongsu
Abstract We examined the possibility of an environment‐friendly slow‐release fertilizer (SRF) made of biochar impregnated by anaerobically digested slurry. The biochar materials were produced from three types of feedstocks (orange peel, residual wood, water‐treatment sludge) at different temperatures of 300°C, 500°C, and 700°C via pyrolysis. The release behaviors of the water‐soluble K+, Ca2+, and Mg2+ were similar for all impregnated biochars and the commercial SRF used. The water‐retention capacity was greatly improved by mixing the biochar‐SRF with the soil. The yield of lettuce was lower for the biochar‐SRF applications of 3.7 to 34.2 t ha–1 than for the commercial SRF application of 51.4 t ha–1. This might be due to excessive increase of soil pH for the biochar‐SRF application. Based on these results, the authors concluded that the biochar impregnated with nutrients could become an effective slow‐release K+ fertilizer.